Towards developing a theoretical framework on career success of people with disabilities - Abdul Wahat, Nor Wahiza (Canadian Center of Science and Education, 2011)
Malaysian workforce is increasingly encompassed by a group of minority who are incapacitated due to some illness or perhaps an accident. They are known as the people with disabilities (PWDs). More attention and initiatives are now built for the PWDs, thus leading to the assumption that they should be enjoying better level of career success. Thus, the purpose of this paper is to develop a theoretical framework for measuring PWD’s career success based on the integration of sponsored mobility model of career success and person environment perspective. Suggested predictive potential of four key factors on PWD’s career success are person-job fit perception, needs-supplies fit perception, core self-evaluation and universal work environment. The developed theoretical framework would lead to an empirical study on objective and subjective career success of PWDs in Malaysia. The framework suggests specific individual attribute, personality and perception can lead to better objective and subjective career success. PWDs having positive core self-evaluation, higher levels of person-job fit and needs-supplies fit perception are believed to achieved better career outcomes, that is objective and subjective career success.